Basic Mechanics of Lagrange and Hamilton as Reference for STEM Students - Budiman Nasution; Lulut Alfaris; Ruben Cornelius Siagian (Jurnal Penelitian Pendidikan IPA, 2023)
This paper discusses the use of Lagrangian and Hamiltonian dynamics as alternative approaches for understanding the motion of objects in classical mechanics. These approaches, which are based on different mathematical techniques, can provide a deeper understanding of the principles of classical mechanics and the motion of objects, but may not be covered in high school physics curricula or undergraduate STEM courses. The review paper approach is used to combine information from a variety of sources, and the material is conceptualized to aid reader understanding. These advanced topics may be of interest to advanced high school students who are interested in exploring topics beyond the high school physics curriculum, and can be studied independently by those with a strong foundation in classical mechanics and familiarity with advanced mathematical concepts.